Pluripotent Stem Cells Induced from Testicular Tissue of a Man with Klinefelter Syndrome (47, XXY) by Four Transcription Factors (OCT4, SOX2, KLF4, and C-MYC) - Kobayashi, Hideyuki (IntechOpen, 2011)
None